Psycho-Personological Correlates of Academic Help-Seeking Among In-School Adolescents - Habeeb Omoponle Adewuyi; Veronica Dwarika (Studies in Learning and Teaching, 2023)
In the field of educational psychology, seeking academic help is a proven success strategy. This study examined the influence of emotional stability, self-esteem, and gender on academic help-seeking among in-school adolescents in Osun state. The descriptive correlational research design was used. The multi-stage sampling method was used by the researchers. Four hundred (400) in-school adolescents were used for the study. The data for this study were gathered using three reliable and standardized instruments: The Academic Help-seeking Behavior Rating Scale (α = .77), the Emotional Stability Scale (α = .88), and Self-esteem Scale (α = .72). The results demonstrated a substantial correlation between academic help-seeking among in-school adolescents and emotional stability (r = .146; p<.05), self-esteem (r = .207; p<.05), and gender (r = .025; p>.05) which was not significant. All the independent variables jointly contributed to academic help-seeking among in-school adolescents. Self-esteem made the most significant contribution (β = .249; t = 5.049; p<0.05) to academic help-seeking followed by emotional stability (β = .198; t= 4.016; p<0.05) and Gender (β = .032; t = 6676; p>0.05). It was recommended that educational psychologists should assist in raising awareness and providing counseling to students who have poor or low academic help-seeking behavior.